2011
DOI: 10.1007/s11064-011-0402-9
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord-Derived Schwann-Like Cell Transplantation Combined with Neurotrophin-3 Administration in Dyskinesia of Rats with Spinal Cord Injury

Abstract: Mesenchymal stem cells are capable of differentiating into Schwann-like cells. In this study, we induced human umbilical-cord mesenchymal stem cells (HUMSCs) in vitro into neurospheres constituted by neural stem-like cells, and further into cells bearing strong morphological, phenotypic and functional resemblances with Schwann-like cells. These HUMSC-derived Schwann-like cells, after grafting into the injured area of the rats' spinal cord injury (SCI), showed a partial therapeutic effect in terms of improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Genetic modification of UC-MSCs with NT-3 further enhanced their therapeutic effectsafter clip injury to the spinal cord [35]. Injection of Schwann-like cells induced from UC-MSCs, combined with NT-3 administration, further promoted the survival of UC-MSCs and functional recovery [36]. A combination treatment of Taxol and UC-MSCs for spinal cord injury further reduced the extent of astrocyte activation, increased axonal preservation, decreased the number of caspase-3(+) and ED-1(+) cells, and enhanced functional recovery compared with UC-MSC treatment alone [37].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic modification of UC-MSCs with NT-3 further enhanced their therapeutic effectsafter clip injury to the spinal cord [35]. Injection of Schwann-like cells induced from UC-MSCs, combined with NT-3 administration, further promoted the survival of UC-MSCs and functional recovery [36]. A combination treatment of Taxol and UC-MSCs for spinal cord injury further reduced the extent of astrocyte activation, increased axonal preservation, decreased the number of caspase-3(+) and ED-1(+) cells, and enhanced functional recovery compared with UC-MSC treatment alone [37].…”
Section: Discussionmentioning
confidence: 99%
“…7 Stem cell transplantation is a promising candidate to treat SCI. [8][9][10][11][12] Recent work showed that stem cells, such as mesenchymal stem cells (MSCs), [13][14][15] neural stem/progenitor cells (NS/ PCs), 16,17 and embryonic stem cells (ESCs), [18][19][20] have immunoregulatory capacity and anti-inflammatory effects and could enhance functional improvement through inducing macrophages M1/M2 phenotype transformation post SCI. This review will discuss 1) the general feature of macrophages in response to SCI, 2) the phenotype and function of macrophages in SCI, and 3) the effects of stem cells on macrophage polarization and its role in stem cell-based therapies for SCI.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of this protocol has been repeated and confirmed by other research groups (Hou 2006;Keilhoff 2006;Tohill 2004;Xu 2011b;Zhao 2005). Furthermore, our group (Matsuse 2010) and other research groups (Jiang 2008;Kingham 2007;Peng 2011;Xu 2008;2011a;Yan-Wu 2011) showed that other types of mesenchymal stem cells, human umbilical cord-derived mesenchymal stem cells, and adipose-derived stem cells, have also been shown to differentiate into Schwann cells by our original method or with minor change. However, our original protocol stands as general standard for Schwann cell induction from mesenchymal stem cells.…”
Section: Introductionmentioning
confidence: 92%